A Fuzzy Robust Controller for Robotic Systems - Alnufaie, Lafi (International Journal of Advanced Engineering Research and Science, 2023)
In this work a combination of type 2 fuzzy logic and nonsingular fast sliding mode technique is proposed to design a robust controller for a robotic system. Indeed, a nominal type 2 fuzzy model is used to contract the equivalent control signal. The switching signal is designed using adaptive type 2 fuzzy systems to overcome the knowledge of the upper bounds of uncertainties and external disturbances. Several simulation results are given to show the efficiency of the proposed approach.